2019
DOI: 10.14198/obets2019.14.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad sexual: imaginarios y actitudes en estudiantes de enseñanzas medias y superiores mexicanos

Abstract: The sex-gender system refers to a process through which the population is socially dichotomizes, stereotypes and hierarchized. Taking into consideration 20 university and pre-university students, a qualitative research is proposed to identify the social perception they have about homosexuality, bisexuality and transsexuality and to analyse its possible effects on health. The results show that there is a great amont of myths, stereotypes and stigmatizing perceptions among young people. Therefore, it is consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
1
0
3
Order By: Relevance
“…Women are the people who show more positive attitudes in both factors, and men are the people with more negative attitudes. These results are consistent with research, where a higher proportion of negative attitudes were found in men than in women, including a Mexican study, in which worse attitudes were observed in men with a higher educational level, and stereotyped ideas were detected [9,[13][14][15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Women are the people who show more positive attitudes in both factors, and men are the people with more negative attitudes. These results are consistent with research, where a higher proportion of negative attitudes were found in men than in women, including a Mexican study, in which worse attitudes were observed in men with a higher educational level, and stereotyped ideas were detected [9,[13][14][15].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it is observed that myths and stereotypes have a smaller impact regarding transgender identity in women and pre-university students. On the other hand, the most negative attitudes were registered in men and university students [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Demostrando la necesidad de eliminar este tipo de conductas a través del fomento de una educación integral que abarque la sexualidad, y aunque la niñez es el mejor momento para iniciar esta sensibilización, en el nivel universitario también pueden desarrollarse acciones que sumen a transformar los patrones valorativos hacia las diferencias que existen entre todos los individuos 26 .…”
Section: Discussionunclassified
“…Lo anterior dio paso para establecer una comparación entre cinco artículos que guardan similitud con el fenómeno estudiado (18,23,24,26,28) , donde se encuentra un punto de semejanza en cuanto a los principales comportamientos homofóbicos en los estudiantes, sobresaliendo la intolerancia, machismo, invisibilidad, incomodidad, discriminación y el estigma que existe hacia las personas LGBTTTIQ+. A pesar de que esta investigación obtuvo resultados favorables hacia el nivel de homofobia, se encontró similitud en diversos comportamientos hacia las minorías, como que un 26,0% de los jóvenes opina que respeta a los gays siempre y cuando no se exhiban o que el 5,6% afirmó que serían capaces de agredir a una persona de su mismo sexo si intenta ligarlos.…”
Section: Discussionunclassified
“…El abordaje sociológico de los estudios sobre el VIH desde una perspectiva epistemológica constructivista, incluye el análisis de los mecanismos de producción y reproducción del estigma asociado al VIH; en los cuales se constata la conjugación de factores, tanto micro como macrosociales, que operan en los procesos de estigmatización. Estos procesos, como señalan Rodríguez y Facal (2019), hacen referencia a mecanismos basados en un sistema jerárquico de poder (con base en la hegemonía de ciertas identidades), los cuales, a través de diferentes procesos de socialización y ritualización, promueven la devaluación de ciertos atributos o características identitarias adyacentes y (re) producen la discriminación, la estratificación social y por ende la desigualdad social (Parker, 2012). No obstante, como indican Major y O'Brien (2005), en tales procesos resultan determinantes: (1) la configuración de las representaciones colectivas, las señales situacionales y las características personales, (2) las evaluaciones de las amenazas de identidad, (5) la presentación de respuestas voluntarias e involuntarias a las amenazas a la identidad y (6) el afrontamiento en respuesta a las amenazas a uno mismo.…”
Section: Introductionunclassified